Power Struggles in the Remembering of Historical Intergroup Conflict: Hegemonic and Counter-Narratives About the Argentine “Conquest of the Desert” - Barreiro, Alicia Viviana (2017)
In this chapter, we examine laypeople’s narratives about historical processes, collectively constructed, transacted, and transmitted in an effort to remember and make sense of past events, and focus on the constitutive relations between hegemonic and counter-narratives. We rely on concrete examples of narratives about a specific process drawn from Argentine history, the “Conquest of the Desert”. Our aim is to underscore some of the tensions and contradictions that arise in recollections and retellings of historical processes, as well as their implications for the construction of collective identities and intergroup relations.